Find the Y-Intercept y=1/3*(-3)

Math
y=13⋅(-3)
Rewrite in slope-intercept form.
Tap for more steps…
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Cancel the common factor of 3.
Tap for more steps…
Factor 3 out of -3.
y=13⋅(3(-1))
Cancel the common factor.
y=13⋅(3⋅-1)
Rewrite the expression.
y=-1
y=-1
y=-1
Using the slope-intercept form, the y-intercept is -1.
b=-1
Find the Y-Intercept y=1/3*(-3)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top